Erratum: YAP determines the cell fate of injured mouse hepatocytes in vivo - Norio Miyamura (Nature Portfolio, 2017)
Nature Communications 8 Article number: 16017 (2017); Published: 6 July 2017; Updated: 7 August 2017. The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: This work was supported by a Nanken-Kyoten grant from Tokyo Medical and Dental University (TMDU).